2017
DOI: 10.1073/pnas.1616602114
|View full text |Cite
|
Sign up to set email alerts
|

Dual-utility NLS drives RNF169-dependent DNA damage responses

Abstract: Loading of p53-binding protein 1 (53BP1) and receptor-associated protein 80 (RAP80) at DNA double-strand breaks (DSBs) drives cell cycle checkpoint activation but is counterproductive to high-fidelity DNA repair. ring finger protein 169 (RNF169) maintains the balance by limiting the deposition of DNA damage mediator proteins at the damaged chromatin. We report here that this attribute is accomplished, in part, by a predicted nuclear localization signal (NLS) that not only shuttles RNF169 into the nucleus but a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
49
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(56 citation statements)
references
References 52 publications
5
49
2
Order By: Relevance
“…S3D) 64 . Taken together, these results indicate that DYRK1A expression and activity are required for efficient 53BP1 recruitment to DSBs within one hour, which contrasts with the reported role for RNF169 in antagonizing 53BP1 recruitment to promote HR and SSA 50,52 .…”
Section: Resolution Of 53bp1 Foci Was Measured By Quantifying the Deccontrasting
confidence: 77%
“…S3D) 64 . Taken together, these results indicate that DYRK1A expression and activity are required for efficient 53BP1 recruitment to DSBs within one hour, which contrasts with the reported role for RNF169 in antagonizing 53BP1 recruitment to promote HR and SSA 50,52 .…”
Section: Resolution Of 53bp1 Foci Was Measured By Quantifying the Deccontrasting
confidence: 77%
“…Further proteomic studies of the RNF169-DYRK1A complex in the cells before and after DNA damage will help to identify such factor. Our analysis of DYRK1A detected interaction with USP7, a ubiquitin-specific protease that has been recently shown to bind directly to RNF169 and to increase the stability of 53BP1, RNF169 and RNF168 (An et al, 2017; Liu et al, 2016; Yim et al, 2017; Zhu et al, 2015). Although disruption of the DYRK1A phosphorylation sites in RNF169 did not influence its interaction with USP7, the role of USP7 in the DYRK1A-RNF169 mediated regulation of 53BP1 should be further investigated.…”
Section: Discussionmentioning
confidence: 82%
“…Both the RNF169-AA and RNF169-DD mutants were able to bind polyubiquitin chains similar to the wild type RNF169, further supporting our conclusion that S368 and S403 sites do not play a role in RNF169’s accumulation at the DSB sites (Figure S3E). Furthermore, mutations of these sites did not affect the interaction with ubiquitin-specific protease USP7 that has been shown to be important for RNF169 function in DNA repair (An et al, 2017) (Figure S3F). Therefore, our data presented above support the conclusion that the intact S368 and S403 sites in RNF169, together with the DYRK1A kinase activity, are required for RNF169 to fully exert its ability to limit the recruitment of 53BP1 at the DSB sites after γ-radiation, through a mechanism unrelated to recognition of the ubiquitylated chromatin or USP7 binding by RNF169.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The MS analysis of the protein band specific to PRLH1 RNA revealed that RNF169 specifically bound to PRLH1 with the highest and most significant score among 10 detected proteins ( Fig 4B and Appendix Table S1). RNF169 is an E3 ubiquitin ligase that has been reported as a negative regulator of the ubiquitin-dependent DNA damage signaling cascade and is involved in HR-mediated DNA repair [11,48,49].…”
Section: Prlh1 Specifically Binds To the Dna Repair Protein Rnf169mentioning
confidence: 99%